2012
DOI: 10.1371/journal.pone.0050928
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Selenite Improves Folliculogenesis in Radiation-Induced Ovarian Failure: A Mechanistic Approach

Abstract: Radiotherapy is a major factor contributing to female infertility by inducing premature ovarian failure (POF). Therefore, the need for an effective radioprotective agent is evident. The present study investigated the mechanism of potential radioprotective effect of sodium selenite on radiation-induced ovarian failure and whether sodium selenite can stimulate in-vivo follicular development in experimental rats. Immature female Sprague-Dawely rats were either exposed to gamma-radiation (3.2 Gy, LD20), once and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 60 publications
4
30
0
Order By: Relevance
“…Present results indicated that oocytes contained in primordial follicles were particularly sensitive to ionizing radiation, whereas growing oocytes were comparatively radio resistant. These findings are in agreement with Said et al (2012) who found that irradiation induce almost complete deletion of the primordial follicle pool within a time period of 24-hrs in contrast to the other growing antral follicles.…”
Section: Resultssupporting
confidence: 93%
“…Present results indicated that oocytes contained in primordial follicles were particularly sensitive to ionizing radiation, whereas growing oocytes were comparatively radio resistant. These findings are in agreement with Said et al (2012) who found that irradiation induce almost complete deletion of the primordial follicle pool within a time period of 24-hrs in contrast to the other growing antral follicles.…”
Section: Resultssupporting
confidence: 93%
“…Protective effect of Se may improve pregnancy rates and reached to 100%. These studies have confirmed a link between antioxidant-poor diet and pregnancy loss (Said et al, 2012).…”
Section: Conception and Pregnancy Ratementioning
confidence: 54%
“…+ Sodium Selenite 0.50 mg/kg b.w. (Said et al, 2012). At the end of experiment, animals were sacrificed and tissues (testis, epididymis, uterus, ovary, liver and kidney) were taken for histopathological, histochemical and immunopathological examinations.…”
Section: Animal Groups and Dose Administrationmentioning
confidence: 99%
“…Many studies demonstrated that, the damaging properties of γ-radiation within biological systems are intermediated by the production of ROS in cells after water radiolysis (Kamat et al, 2000 andSaid et al, 2012). The generated ROS destroy important biological molecules for instance nucleic acid, proteins, lipids as well as cell membranes (Maurya and Devasagayam, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy (RT) is considered as a curative medical intervention, depends on the generation and uses of reactive oxygen species (ROS) to eradicate tumours but non-target tissues are also damaged (Said et al, 2012). RT is a major factor contributing to male infertility by destroying the process of spermatogenesis (Ahmed and Tawfik, 2012).…”
mentioning
confidence: 99%